SOME QUESTIONS TO ENSURE THE AUTHENTICITY OF INTERNATIONAL TREATIES - Shyngysbayeya , Дүйсенкүл Мұқамбетжанқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article describesthe issues of ensuring the authenticity of texts of the projects of international treaties.